Transcutaneous auricular vagal nerve stimulation for consciousness recovery in patients with prolonged disorders of consciousness (TAVREC): study protocol for a multicenter, triple-blind, randomized controlled trial in China - Jan D Reinhardt; Jin Liu; Ting Luo; Xiao Lu; Zhen-Yu Liu; Long-yun Zhou; Li-jun Peng; Ya-feng Liu; Shu-wei Wang; Yue Qiu; Si-jing Chen; Ming-ming Feng; et al. (BMJ Open)
Introduction Prolonged disorders of consciousness (pDoC) are a catastrophic condition following brain injury with few therapeutic options. Transcutaneous auricular vagal nerve stimulation (taVNS), a safe, non-invasive intervention modulating thalamo-cortical connectivity and brain function, is a possible treatment option of pDoC. We developed a protocol for a randomised controlled study to evaluate the effectiveness of taVNS on consciousness recovery in patients with pDoC (TAVREC).Methods and analysis The TAVREC programme is a multicentre, triple-blind, randomised controlled trial with 4 weeks intervention followed by 4 weeks follow-up period. A minimum number of 116 eligible pDoC patients will be recruited and randomly receive either: (1) conventional therapy plus taVNS (30 s monophasic square current of pulse width 300 μs, frequency of 25 Hz and intensity of 1 mA followed by 30 s rest, 60 min, two times per day, for 4 weeks); or (2) conventional therapy plus taVNS placebo. Primary outcome of TAVREC is the rate of improved consciousness level based on the Coma Recovery Scale-Revised (CRS-R) at week 4. Secondary outcomes are CRS-R total and subscale scores, Glasgow Coma Scale score, Full Outline of UnResponsiveness score, ECG parameters, brainstem auditory evoked potential, upper somatosensory evoked potential, neuroimaging parameters from positron emission tomography/functional MRI, serum biomarkers associated with consciousness level and adverse events.Ethics and dissemination This study was reviewed and approved by the Research Ethics Committee of the First Affiliated Hospital of Nanjing Medical University (Reference number: 2023-SR-392). Findings will be disseminated in a peer-reviewed journal and presented at relevant conferences.Trial registration number ChiCTR2300073950.